THE EFFECT OF NATURE OF INDUSTRY, FINANCIAL STABILITY, INEFFECTIVE MONITORING, AND CHANGES IN COMPANY DIRECTORS ON INDICATIONS OF FRAUDULENT FINANCIAL STATEMENTS - Musfi, Putri Nabila; Soemantri, Roebiandini (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2024)
Fraudulent financial statements are part of corporate management fraud. It is conducted based on the financial condition of the organization for the purpose of misleading users of financial statements by omitting values or amounts in the disclosure of financial statement documents. Therefore, it will mislead the stakeholders who are investing in the company. This study aims to analyze the effect of the nature of the industry, financial stability, ineffective monitoring, and changes in company directors on indications of fraudulent financial statements. The research population is manufacturing sector companies listed on the Indonesia Stock Exchange (IDX) for the 2017–2019 period, which are listed on the website www.idx.co.id. There are as many as 183 companies. The sampling method used is the purposive sampling method. The companies that meet the sampling criteria are 76. The analysis tool uses multiple linear regression tests. The results of this study indicate that the nature of the industry has a positive effect on indications of fraudulent financial statements, financial stability has a positive effect on indications of fraudulent financial statements, and ineffective monitoring has a positive effect on indications of fraudulent financial statements. Meanwhile, the changes in company directors has no effect on indications of fraudulent financial statements.